2010
DOI: 10.1002/jcb.22791
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin inhibits osteoclastogenesis while enhancing osteoclast activity via nitric oxide and interleukin‐1β‐mediated signaling pathways

Abstract: Osteoclasts are bone-resorbing cells formed by fusion of mononuclear precursors. The matrix proteins, fibronectin (FN), vitronectin (VN), and osteopontin (OPN) are implicated in joint destruction and interact with osteoclasts mainly through integrins. To assess the effects of these matrix proteins on osteoclast formation and activity, we used RAW 264.7 (RAW) cells and mouse splenocytes differentiated into osteoclasts on tissue culture polystyrene (TCP) or osteologic™ slides pre-coated with 0.01-20 µg/ml FN, VN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Integrin β3 protein was not identified, and mRNA encoding integrin β3 was found to be unchanged during differentiation. Integrin α5β1 is involved in recognizing fibronectin, a bone matrix protein ( 56 ), and although the expression of integrin α5 mRNA and protein increased in the IOs and OCs, protein expression of integrin β1 was down-regulated, and mRNA of β1 was unchanged in these cells. In general, the expression of integrin α chain showed good correlation between mRNA and protein, but that of integrin β chain did not.…”
Section: Resultsmentioning
confidence: 99%
“…Integrin β3 protein was not identified, and mRNA encoding integrin β3 was found to be unchanged during differentiation. Integrin α5β1 is involved in recognizing fibronectin, a bone matrix protein ( 56 ), and although the expression of integrin α5 mRNA and protein increased in the IOs and OCs, protein expression of integrin β1 was down-regulated, and mRNA of β1 was unchanged in these cells. In general, the expression of integrin α chain showed good correlation between mRNA and protein, but that of integrin β chain did not.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that while the ECM proteins FN and VN decreased the number of osteoclast formed by ∼ 65%, OPN promoted osteoclast formation. Although the ECM proteins modulated osteoclast formation, none of these proteins affected RAW cell viability [Gramoun et al, in preparation].…”
Section: Resultsmentioning
confidence: 99%
“…Previous literature has also shown that fibronectin inhibits osteoclast differentiation activity, but stimulates function through IL-1β and nitric oxide. 57 Interestingly, fibronectin has been found to bind CD44 through its heparin-binding domain. 58 It will be interesting to determine if CD44, Osteoactivin and fibronectin have any interaction or involvement in osteoclast differentiation and function.…”
Section: Discussionmentioning
confidence: 99%